2010
DOI: 10.1021/ml100058w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism-Guided Design of Short-Acting Calcium-Sensing Receptor Antagonists

Abstract: As part of a strategy to deliver short-acting calcium-sensing receptor (CaSR) antagonists, the metabolically labile thiomethyl functionality was incorporated into the zwitterionic amino alcohol derivative 3 with the hope of increasing human clearance through oxidative metabolism, while delivering a pharmacologically inactive sulfoxide metabolite. The effort led to the identification of thioanisoles 22 and 23 as potent and orally active CaSR antagonists with a rapid onset of action and short pharmacokinetic hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…For a sharp peak in the time-plasma concentration profile these parameters play an important role. Introduction of a metabolically labile thiomethyl functionality (soft-drug concept [46]) afforded compound 5 (FiguRe 4), with high potency (IC 50 = 5 nM), a bioavailability of 28% in rats and a sharp PTH peak (baseline reached within 2 hours postdose [47]). …”
Section: Amino Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a sharp peak in the time-plasma concentration profile these parameters play an important role. Introduction of a metabolically labile thiomethyl functionality (soft-drug concept [46]) afforded compound 5 (FiguRe 4), with high potency (IC 50 = 5 nM), a bioavailability of 28% in rats and a sharp PTH peak (baseline reached within 2 hours postdose [47]). …”
Section: Amino Alcoholsmentioning
confidence: 99%
“…Therefore, PTH (albeit in lower amounts) is released beyond a 1-2-h period postdosing, widely considered to be the limit for bone anabolic effects. An attractive way to circumvent these problems may be the concept of soft drugs [46,47].…”
Section: Future Perspectivementioning
confidence: 99%
“…The strategic introduction of a nitrogen atom into the phenol ring of 256 to give 258 was anticipated to reduce the rate of metabolic activation of the catechol based on quantum chemistry calculations which indicated that oxidation of the aza-catechol derived from 258 to the corresponding quinone was energetically less favorable than for 257 . This was confirmed experimentally with a 50-fold reduction in the formation of GSH adducts compared to 256 when 258 was incubated in liver microsomes [ 363 , 364 ]. …”
Section: Isosteres To Address Metabolism and Toxicitymentioning
confidence: 71%
“…The phenol 256 is a short-acting calcium-sensing receptor antagonist that was examined for its potential as a treatment for osteoporosis [ 363 , 364 ]. However, CYP 3A4-mediated oxidation of the phenol ring of 256 afforded the catechol 257 which underwent further oxidation to the corresponding ortho quinone, a metabolite identified as the source of GSH adducts in both human and rat liver microsomes.…”
Section: Isosteres To Address Metabolism and Toxicitymentioning
confidence: 99%
“…含有 2-甲基-1-取代苯基-2-丙胺的结构单元存在于 许多生物活性分子中, 例如, 用于治疗抑郁症的胃饥饿 素受体拮抗剂 ghrelin receptor antagonists [1] 、 用于治疗胃 肠道和心血管疾病的钙敏感受体抑制剂 CaSR antagonists [2] 、用于治疗肥胖症的 β 3 肾上腺素受体激动剂 LY377604 [3,4] 以 及 长 效 β 2 肾 上 腺 素 受 体 激 动 剂 BI167107(图 1) [5~7] . …”
unclassified